Comparative evaluation of Willems and Cameriere methods of dental age estimation among 6–14 year old Bengali children - Mehuli Kar; Aruna Sharma; Kaushik Dutta; Rekha Puttanavar; Sanguida A; Ezhumalai Govindasamy (Journal of Oral Biology and Craniofacial Research)
Background: The knowledge of dental age estimation is essential to assess growth and development which aids in designing a treatment plan. Willems and Cameriere methods are the two most widely used approaches of dental age estimation. Aim: The primary objective of this study was to evaluate the reliability and applicability of the two methods, among 6–14 year old children of Bengal populace. The secondary objective was to compare the efficacy of Sante DICOM Viewer and CorelDRAW Graphic Suite in assessing dental age by Cameriere method. Materials and methods: The study sample encompassed 411 digital panoramic radiographs. Dental age was estimated using Willems and Cameriere methods. CorelDRAW Graphic Suite and Sante DICOM Viewer software were used for dental age estimation by Cameriere method. Paired t-test was applied for the inter group comparison. Pearson correlation coefficient was also used to measure the regression among all the groups. Results: Dental age was overestimated by 0.286 years using Willems method (p = 0.001). However, there was no significant difference between dental ages estimated by Cameriere method using both software (p = 0.130). Conclusion: Both the methods were equally applicable for age estimation in the targeted population. Cameriere method can be performed with equivalent accuracy using both software.